Pengembangan Buku Petunjuk Praktikum pada Matakuliah Fisiologi Tumbuhan I - Hakim, Arief Rahman (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2024)
The aim of this research is to develop a practical manual for the Plant Physiology I course. This research is included in development research. The design used in this research uses a 4D model which was adapted into a 3P model (Definition, Design and Development). The research instruments used were validation sheets and readability test sheets. This development research uses two expert validators, namely content/material experts and teaching materials experts as well as readability tests by students. Data collection techniques use validation techniques and readability tests. The data analysis technique used is the percentage technique. The research results showed that the value of the content/material expert validator was an average of 3.15, the teaching material expert validator was an average of 3.11, and the readability test by 20 students was an average of 3.08. Thus, teaching materials in the form of a Plant Physiology I practical manual are suitable for use without revision.